Dynamic control strategy of a distillation system for a composition-adjustable organic Rankine cycle. (15th December 2017) - Wang, Enhua; Yu, Zhibin; Collings, Peter
Abstract: Using zeotropic mixtures as working fluids can improve the thermal efficiency of Organic Rankine cycle (ORC) power plants for utilising geothermal energy. However, currently, such ORC systems cannot regulate the composition of zeotropic mixtures when their operating conditions change. A composition-adjustable ORC system could potentially improve the thermal efficiency by closely matching the cycle to the changing ambient conditions provided that the composition of the working fluid mixture can be adjusted in an economic way. In this paper, a dynamic composition control strategy has been proposed and analysed for such a composition-adjustable ORC system. This method employs a distillation column to separate the two components of the mixture, which can then be pumped back to the main ORC system to adjust the composition of the zeotropic mixture to the required level according to the ambient temperature. The dynamic composition control strategy is simulated using an optimisation algorithm. The design method of the distillation column is presented and its dynamic response characteristics have been analysed using Aspen Plus Dynamics. The results indicate that the average power output can be significantly improved using a composition-adjustable ORC system when the ambient temperature decreases. The size of the distillation system is relatively small and its energy (mainly thermal) consumption is only around 1% of the system's input heat. The research results also show that the dynamic response characteristics of the distillation system can satisfy the requirements of the ORC system. Highlights: A composition-tuning system is proposed for a composition-adjustable ORC. A dynamic composition control strategy for distillation system is designed. A distillation system is simulated, designed and analysed using Aspen Plus. The response characteristics of the distillation system meet the requirement.